Linkage analysis of glucokinase gene with NIDDM in Caucasian pedigrees. - Cook,JT; Hattersley,AT; Christopher,P; Bown,E; Barrow,B; Patel,P; Shaw,JA; Cookson,WO; Permutt,MA; Turner,RC (Diabetes, 1992)
NIDDM has a strong genetic component, as evidenced by the high level of concordance between identical twins. The nature of the genetic predisposition has remained largely unknown. Recently, the glucokinase gene locus on chromosome 7p has been shown to be linked to a subtype of NIDDM known as MODY in French and British pedigrees, and glucokinase mutations have been identified. To study the relationship between the glucokinase gene and NIDDM, we performed a linkage analysis in 12 Caucasian pedigrees ascertained through a proband with classical NIDDM. The LINKAGE program was used under four models, including autosomal dominant and recessive, with individuals with glucose intolerance counted as either affected or of unknown status. Linkage was significantly rejected with the dominant models (LOD scores -4.65, -4.25), and was unlikely with the recessive model when glucose intolerance was considered as affected (LOD score -1.38). These findings suggest that mutations in or near the glucokinase gene are unlikely to be the major cause of the inherited predisposition to NIDDM in Caucasian pedigrees, but do not exclude a role for this locus with a polygenic model, or a major role in some pedigrees.